Indigenous people's perception of indigenous agricultural knowledge for climate change adaptation in Khumbu, Nepal - Sherpa, Tshering Ongmu (Frontiers in Climate, 2023)
The importance of indigenous knowledge has been gaining traction in recent years. Still, the deep-rooted negative and obsolete connotations associated with its use inhibit its integration with the modern scientific knowledge. It is imperative to provide concrete evidence to rationalize the importance of such dynamic knowledge to formulate effective climate change adaptation strategies. Yet, there is a dearth of empirical work on indigenous people's perception of the effectiveness of indigenous farming knowledge and practices for climate change adaptation, especially in the mountain region. Existing scholarships in Nepal are concentrated on people’s perception of climate change and verifying the effects of socio-economic variables on adopting adaptation strategies. There is a lack of application of a socio-psychological model to scrutinize subjective and cognitive factors influencing adaptation. This study aims to utilize the Protection Motivation Theory (PMT) to provide insights into the risk perception of climate change and the perception of adaptation efficacy of indigenous farming knowledge and practices. A randomly sampled questionnaire survey and focus group discussions were conducted in five villages in the Khumbu region of Nepal. The results indicated that indigenous peoples had observed changes in seasonality, a decrease in snowfall frequency, and an increase in rainfall, posing a significant threat to their lives and livelihood. The perception of adaptation efficacy assessment disclosed that indigenous knowledge is effective in adapting to changing climatic conditions. It was found that the knowledge has been evolving and remains dynamic and relevant even in the backdrop of climate change. The high risk perception and positive perception of adaptation efficacy regarding indigenous farming knowledge signal potential intention of adapting to climate change. However, there is a lack of formal recognition of indigenous knowledge by the government authorities. Hence, the study's findings accredit the significance of indigenous knowledge. From the viewpoint of the generational succession of knowledge and devising cost-effective climate change adaptation strategy, it indicates a dire need for its incorporation into local climate policies and action plans.